Association between ethnicity and under-5 mortality: analysis of data from demographic surveys from 36 low-income and middle-income countries. Issue 3 (March 2020) - Victora, Cesar G; Barros, Aluisio J D; Blumenberg, Cauane; Costa, Janaina Calu; Vidaletti, Luis Paulo; Wehrmeister, Fernando C; Masquelier, Bruno; Hug, Lucia; You, Danzhen
Summary: Background: The UN Sustainable Development Goals (SDGs) call for stratification of social indicators by ethnic groups; however, no recent multicountry analyses on ethnicity and child survival have been done in low-income and middle-income countries (LMICs). Methods: We used data from Demographic and Health Surveys and Multiple Indicator Cluster Surveys collected between 2010 and 2016, from LMICs that provided birth histories and information on ethnicity or a proxy variable. We calculated neonatal (age 0–27 days), post-neonatal (age 28–364 days), child (age 1–4 years), and under-5 mortality rates (U5MRs) for each ethnic group within each country. We assessed differences in mortality between ethnic groups using a likelihood ratio test, Theil's index, and between-group variance. We used multivariable analyses of U5MR by ethnicity to adjust for household wealth, maternal education, and urban–rural residence. Findings: We included data from 36 LMICs, which included 2 812 381 livebirths among 415 ethnic groups. In 25 countries, significant differences in U5MR by ethnic group were identified (all p<0·05 likelihood ratio test). In these countries, the median mortality ratio between the ethnic groups with the highest and lowest U5MRs was 3·3 (IQR 2·1–5·2; range 1·5–8·5), whereas among the remaining 11 countries, the median U5MR ratio was 1·9 (IQR 1·7–2·5; range 1·4–10·0). Ethnic gaps were wider for child mortality than for neonatal or post-neonatal mortality. In nearly all countries, adjustment for wealth, education, and place of residence did not affect ethnic gaps in mortality, with the exception of Guatemala, India, Laos, and Nigeria. The largest ethnic group did not have the lowest U5MR in any of the countries studied. Interpretation: Significant ethnic disparities in child survival were identified in more than two-thirds of the countries studied. Regular analyses of ethnic disparities are essential for monitoring trends, targeting, and assessing the impact of health interventions. Such analyses will contribute to the effort towards leaving no one behind, which is at the centre of the SDGs. Funding: Bill & Melinda Gates Foundation, UNICEF, Wellcome Trust, Associação Brasileira de Saúde Coletiva.